(untitled) - Dương, Ngọc Huyền (Cần Thơ, 2018)
This thesis introduce about describes the context in which the study was carried out, statement of the problem, research questions as well as significance of the study. Presents the literature and the theoretical frameworks on which the study is based. Presents the methodology, participants of the study. Reports the results and discussion of the teachers‘ perceptions of culture in language teaching and their culture teaching practices. Draws the conclusions of the study and presents its contributions, implications, as well as outlining directions for future research
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching